Ultrastructural characterization of ultraviolet induced corneal disease : an animal model - Schultes, Klaus (Division of Cell Biology, 2018)
The majority of ancient people worshipped the sun and viewed it as a health - bringing deity. During the eighteenth and nineteenth century therapeutic benefits of sunlight exposure were beginning to be understood and by the end of the nineteenth century the importance of ultraviolet radiation was being realized. Danish physician Niels Finsen, whom many regard as the father of ultraviolet phototherapy, also stressed that it was ultraviolet radiation in the solar spectrum which cause sunburn. We now recognize that the small portion of ultraviolet radiation which reaches the earth's surface is not necessarily therapeutic, but in fact could be harmful to humans. There are numerous accounts of the harmful effects of UV radiation to the skin and the eye as a whole. These effects may be caused by either acute or chronic exposure to UV radiation. For example, some acute effects of UV-B radiation include conjunctivitis and photokeratitis. "Snow blindness" and "arc welders eye" are further examples of acute ultraviolet damage specifically to the surface of the cornea. On the other hand, chronic exposure to ultraviolet radiation is thought to be responsible for pterygia, climatic droplet keratopathy Hill and Maske (1989), cancers of the external eye, cataracts and various types of retinal diseases. The present study is an extension of ongoing studies on ultraviolet radiation damage to the cornea in the Department of Ophthalmology, University of Cape Town and Groote Schuur Hospital. Their specific interest lies in the causes and treatment of climatic droplet keratopathy. The aims of the present study are: 1) Establish a possible role of ultraviolet B radiation in human corneal diseases such as climatic droplet keratopathy and pterygium using the rabbit as an animal model. 2) Determine by means of SEM the initial effects and subsequent recovery of the epithelium after a 3-hour dose of ultraviolet B radiation. We refer to this study as "acute" response to ultraviolet B radiation. 3) To try and confirm the effects observed by SEM with ultrastructural studies using TEM. 4) In addition, we are also looking at the possible effects after exposing rabbit cornea to a daily dose of low level ultraviolet B radiation, over a long period of time. We refer to this as chronic exposure to ultraviolet B radiation. It is hoped that by exposing rabbits to ultraviolet light, principally ultraviolet B radiation, diseases similar to those found in humans could be simulated and disease progression studied. People are generally exposed to substantial amounts of UV radiation for a very long time. Since people generally live longer they will be exposed to an ever-increasing amount of solar UV radiation and subsequently, there is an increasing risk of developing corneal diseases. The possible threat to the ozone is also a real possibility and could lead to increased levels of ultraviolet radiation reaching the earth's surface. This will require a greater understanding of the very nature of corneal damage due to acute and chronic exposure. This study focusses mainly on the acute response to UV-B radiation since most studies have investigated effects of prolonged exposure to UV light. Accordingly, much less is known about acute exposure. Many people suffering from acute UV B radiation effects probably never visit the ophthalmologist or wait for a couple of days. This could also contribute to the fact that effects of short-term damage is not well documented.